Glomerular Filtration Result in Patients with Hypertensive Emergencies - Manuel Tasis Hernández; Wendy Talavera Hernández; Valentina Edighill Villanueva; Aliucha María Rodríguez Díaz; Taimy Calvera Castro; Juan Francisco Gastón Del Monte (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Foundation: hypertensive emergencies may be the presentation of an underlying chronic kidney disease; in turn kidney damage may be the cause that leads to hypertensive emergency. Theoretical glomerular filtration is recommended to assess the risk of morbidity and mortality in hypertensive emergencies. Objective: to describe the behavior of glomerular filtration in patients with hypertensive emergencies attended at the Julio Trigo López Clinical Hospital in the period of 2016. Methods: a prospective cohort study of patients with hypertensive emergencies attended at the Julio Trigo López Hospital in the 2016-2018 period was performed. A total of 136 patients who met the inclusion criteria were included in the study. Glomerular filtration was calculated and patients were followed up to one year in the hypertension clinic. Results: mean age was 61.6 years (SD ± 13.6 years), prevalence of Fge <60 ml / min / 1.73 m2 was 30.9 %. Patients with kidney damage showed higher mean age (63.5 years; SD ± 13.9 years), higher prevalence of diabetes (61.9 %; OR 5,318; CI9 5 % 2,731 - 6,992; p <0.001), intra and extra hospital mortality 8.8% (OR: 2.44; IC 95 %: 1,933 - 2,902; p <0.001) and 14.5% (RR: 2,264; 95 % CI: 2,151 - 3,476; p <0.001) respectively compared to those without kidney damage. Conclusions: patients with hypertensive emergencies who have kidney damage have a worse prognosis, so a more strict follow-up and treatment are justified.